FEMINIST THEORY AND GENDER DYNAMICS IN CENTRAL ASIAN SOCIETIES (2017-2023) - Nazarillaeva Mekhrangiz (American Journals, 2025)
A perspective through which such a complex sociocultural and political environment may be viewed and contextualized has to incorporate, by necessity, feminist theory when peering into the dynamics within Central Asian societies. Indeed, Central Asia comprises such countries as Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan-each with their diverse history and traditions shaped by the legacy of the Soviet Union, along with growing trends arising from global feminist movements. This paper draws on feminist theoretical frameworks that emphasize the persisting challenges alongside emerging opportunities for gender equality: intersectionality, postcolonial feminism, state feminism, and global feminism. It explores the gendered experiences of women in the region.